Analysis For Improving The Quality Of Education At SMPN 29 Bandar Lampung - Muhammad Sandika Fadly; Muhamad Emil Rachman (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to analyze the improvement in the quality of education at SMPN 29 Bandar Lampung. The informants in this research were 10 students and 20 students at SMPN 29 Bandar Lampung. The analysis method uses IFAS analysis, EFAS analysis, and SWOT analysis. Based on the results of research conducted at SMPN 29 Bandar Lampung above, it can be explained that the thing that must be considered in making a strategy is how an organization is able to formulate a vision, mission and goals that are clear and measurable and then connected to the existing conditions faced (internal environment and external) by determining the resources that constitute the organization's strategic advantage, creating effective and efficient strategies to achieve organizational goals, and the principle in making strategies is how an organization overcomes competition and wins competition by using the resources it has. The following are the strategies that will be used to improve the quality of education at SMPN 29 Bandar Lampung: (1) Equalize the development of student achievement so that students can improve their quality from academic learning and non-academic training to achieve more achievements, thereby increasing the quality of output institution. (2) Make regulations regarding library visits and school principals routinely evaluate and supervise students. (3) Collaborating with the best institutions and improving student achievement by giving appreciation to students.